(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
In the present work cytoplasmic and mitochondrial arginase isoforms (ARG1 and ARG2 respectively) are studied in the rat corticolimbic brain regions in amphetamine induced bipolar disorder (BD). Escalating non-neurotoxic doses of d-amphetamine sulfate (AMPH) injected to rats over 24 days induce changes in behavior mimicking BD accompanied by alterations in resident microbiota with manifestation of pathogenic bacteria. Both ARG1 and ARG2 are stimulated in the brain corticolimbic regions involved in the formation of emotions, learning and memory. Simultaneously, NO stable metabolite levels are diminished or not changed in the cytoplasm and mitochondria of the brain regions studied in AMPH-treated rats. It is suggested that arginase isoforms may contribute the NO-synthase inhibition and prevention of detrimental effects of the reactive nitrogen species overproduced in BD.